Polymide Forward Osmosis Membrane: Synthesis, Characterization, and its Performances for Humic Acid Removal - Mohammad Amirul, Mohd Yusof; Mazrul Nizam, Abu Seman (2015)
In this research, modification on ultrafiltration (UF) membrane by synthesis of a thin layer of polyamide selective layer was designed for high performances of forward osmosis (FO) water treatment. Two monomers, m- Phenylenediamine (MPD) and Trimesoylchloride (TMC) with different concentration of MPD (2.0% w/v and 1.0% w/v) were reacted with TMC (0.15% w/v) for interfacial polymerization (IP) reaction to form a thin polyamide selective layer. The polyamide FO membrane prepared was characterized by using Field Emission Scanning Electron Microscope (FESEM) and contact angle measurement. Forward osmosis membrane performances in term of water flux (L/m2hr) and humic acid rejection (%) were evaluated in order to obtain the best performances of FO membrane. It has been demonstrated that the result of membrane with MPD concentration of 2.0% w/v revealed a large number of fully sponge like structure and posse a high hydrophilic properties. Moreover, experimental results clearly demonstrated that 60s reaction time of polyamide FO membrane with MPD of 2% w/v exhibited lower water flux of 1.98L/m2.h and highest humic acid rejection (99%) when 2.5M of sodium chloride (NaCl) used as draw solution. Compared to 60s reaction time of polyamide FO membrane prepared with MPD concentration of 1.0% w/v with the same concentration of feed and draw solution exhibit a higher water flux, 3.80L/m2 but a lower humic acid rejection with 95.4% of salt rejection was observed. It is found that the overall characterization and performances of the polyamide FO membrane is mainly due to the formation and thickness of the thin polyamide layer that plays an important role in facilitating a high water flux in forward osmosis for humic acid removal.